2013
DOI: 10.1108/tpm-10-2012-0031
|View full text |Cite
|
Sign up to set email alerts
|

Combining old and new tricks: ambidexterity in aerospace design and integration teams

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…In addition, much of the research in the area of ambidexterity has used a macro‐perspective, and only very recently has consideration been given to the group or project team level (Liu and Leitner, ; Fiset and Dostaler, ; Fay et al, ). Indeed, in their introduction to a special issue on the role of HRM in supporting ambidexterity, Junni et al () remarked on the dearth of studies addressing how HRM supports teams in balancing exploitation and exploration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, much of the research in the area of ambidexterity has used a macro‐perspective, and only very recently has consideration been given to the group or project team level (Liu and Leitner, ; Fiset and Dostaler, ; Fay et al, ). Indeed, in their introduction to a special issue on the role of HRM in supporting ambidexterity, Junni et al () remarked on the dearth of studies addressing how HRM supports teams in balancing exploitation and exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Mom et al (2009) found that when organizational procedures promote a manager's decision-making authority, the development of managerial ambidexterity is enhanced. Adding to this, Fiset and Dostaler (2013) empirically showed that a supportive organizational context is positively related with the development of contextual ambidexterity in a project level, which, in turn, enhances the development of schedule adherence performance.…”
Section: Organizationalmentioning
confidence: 94%
“…Speaking up may act as a coordination mechanism that induces flexibility (Kolbe et al, 2012), while itself requiring stability through a team climate of psychological safety (Bienefeld & Grote, 2014b; Nembhard & Edmondson, 2006) and directive leadership (Farh & Chen, 2017). Structural coordination mechanisms, such as performance management systems or role-based requirements for team composition, can set a frame for team behavior that reduces uncertainty and frees cognitive resources for adequately responding to the concurrent demands for reliable performance and exploration (e.g., Ben-Menahem, von Krogh, Erden, & Schneider, 2016; Fiset & Dostaler, 2013; Valentine & Edmondson, 2015). Proposition 1: As both flexibility and stability demands increase, ambidextrous coordination (i.e., personal coordination through both formal and shared leadership and mutual adjustment combined with enabling and constraining structural coordination mechanisms) becomes increasingly positively related to desired adaptive outcomes.…”
Section: A Conceptual Framework For the Dual Nature Of Adaptive Team mentioning
confidence: 99%
“…Considering learning and performance as examples of desired adaptive outcomes, one can speculate that the coordination modes differ in their effects. Ambidextrous and exploratory coordination should have positive effects on both learning and performance (e.g., Fiset & Dostaler, 2013; Gibson & Birkinshaw, 2004; Miron-Spektor & Beenen, 2015). Experiental coordination is more conducive to learning (e.g., Pyrko et al, 2017) and exploitative coordination to performance, although learning may happen as part of continuous minor variations in routines (Feldman & Pentland, 2003) or be prodded by explicit proactivity routines (Vough, Bindl, & Parker, 2017).…”
Section: Integrating the Adaptive Coordination Framework Into A Fullementioning
confidence: 99%